2022
DOI: 10.1371/journal.pone.0276313
|View full text |Cite
|
Sign up to set email alerts
|

Association between XRCC3 p.Thr241Met polymorphism and risk of glioma: A systematic review and meta-analysis

Abstract: Background The XRCC3 p.Thr241Met (rs861539) polymorphism has been extensively studied for its association with glioma risk, but results remain conflicting. Therefore, we performed a systematic review and meta-analysis to resolve this inconsistency. Methods Studies published up to June 10, 2022, were searched in PubMed, Web of Science, Scopus, VIP, Wanfang, and China National Knowledge Infrastructure databases and screened for eligibility. Then, the combined odds ratio (OR) of the included studies was estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…The different observations between different subgroups are not surprising. Many genetic association studies have found significant associations in one ethnic group but not in the others 24–29 . This differential association underscores the interaction between genetic and nongenetic factors in the development of a disease 30 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The different observations between different subgroups are not surprising. Many genetic association studies have found significant associations in one ethnic group but not in the others 24–29 . This differential association underscores the interaction between genetic and nongenetic factors in the development of a disease 30 .…”
Section: Discussionmentioning
confidence: 95%
“…Many genetic association studies have found significant associations in one ethnic group but not in the others. 24 , 25 , 26 , 27 , 28 , 29 This differential association underscores the interaction between genetic and nongenetic factors in the development of a disease. 30 Indeed, longitudinal studies have shown that ethnic‐related differences are present in asthma risk and its outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Besides this, single nucleotide polymorphisms (SNPs) were alos associated with the hearing loss and other diseases ( Antonino et al, 2022 ; Li et al, 2022 ; Tan et al, 2022 ). Meta analysis and screening studies for such genetic markes have shown a strong association of SNPs with hearing loss suggesting their important role in normal functioning and development.…”
Section: Introductionmentioning
confidence: 99%